Strategic Framing Matters But Varies: A Structural Topic Modeling Approach to Analyzing China’s Foreign Propaganda About the 2019 Hong Kong Protests on Twitter - Maggie Mengqing Zhang; Xiao Wang; Yang Hu (SAGE Journals, 2021)
Drawing upon the approach of strategic framing, this study investigated how China’s state-run media mobilize foreign propaganda machine and use specific patterns to describe the 2019 Hong Kong protests on Twitter. It also shed light on the heterogeneity of both production and reception of the strategic frames used by state media. Structural topic modeling was employed to analyze a large amount of Twitter content (i.e., 14,412 tweets) posted by 13 verified organizational accounts, and six strategic frames were identified as conflicts and violence, calling for stability and order, marginalizing protests, criticizing the West as accomplices, delegitimizing protests, and social and economic disruption. These frames highlighted insider–outsider and causes and consequences as two overarching communication strategies. The results also revealed that the bureaucratic rank of state media and the engagement rate of each tweet were closely associated with the content prevalence of various strategic frames. In addition to enhancing our understanding of the construction of “protest paradigm” against the social media context, these empirical findings uncover the often overlooked mobility and flexibility of China’s state media discourse as well as the communication ecology shaped and consolidated by the increasing importance state media communicators attach to online engagement metrics.
Keywords: Science Policy; Sociology